ANALISIS DETERMINAN KEMISKINAN DI PROPINSI NUSA TENGGARA BARAT TAHUN 2016 - Abdul Farid; Hailuddin Hailuddin; Wahyunadi Wahyunadi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
Research entitled Analysis of Poverty determinant in West Nusa Tenggara province for the period of 2010-2016. The research aims to test the influence of: (1) health as indicated by life expectancy for poverty, (2) education is indicated by Length of school average on poverty, (3) investment indicated by the formation of gross fixed capital on poverty, (4) Degree of Fiscal Autonomy towards poverty. So, refers to this aims the government of West Nusa Tenggara province can find out what interventions can be performed toward variables observed to decrease poverty rate. Research method using descriptive analysis with secondary data taken from sources that have legality in issued development data. so we can take quantitative approach to know how much influence of variable observed toward poverty in West Nusa Tenggara Province period of 2010-2016.